Estimating the Impact of Energy Consumption on Carbon Emissions Using Environmental Kuznets Curve - Alanazi, Naif Dalish N.; Dmitriy, Zavyalov; Polyakova, Aleksandra G. (International Journal of Energy Economics and Policy, 2020)
The objective of this study is to examine the equilibrium relationship in the short and long term of energy consumption in Indonesia (ECI) and carbon dioxide emissions in Indonesia (CO2EI) for the period of 1980-2014. The dependent variable is environment and CO2 emissions have been selected as an indicator for this variable while the independent variable in this study is energy consumption. In this study, quantitative method-based methodology has been selected. The quantitative method enable researcher to examine the relationship objectively using numbers, digits, and ratings as empirical evidence. In addition, the researcher used deductive reasoning to present the arguments. Deductive approach was selected because the research aims to test EKC hypotheses and test it within the context of Indonesia and assess whether there is long term relationship between ECM and CO2EM. In order to analyse the panel data, this study used statistical techniques. Firstly, descriptive statistics has been used to assess the central tendency of data using mean and standard deviation. In addition, Dickey Fuller test was performed to check stationarity in the data. Finally, ARDL model was developed to check the impact of independent variables on dependent variable.Through time series models this study found that there is long-term equilibrium relationship between CO2E and EC. Furthermore, it can be concluded that there is a short-term relationship between the variables also. Finally, in general the results show that EC positively influences CO2E in the short and long term. Keywords: Energy Consumption, carbon emissions, Environmental Kuznet Curve, Indonesia JEL Classifications: Q43, Q5 DOI: https://doi.org/10.32479/ijeep.10244